PENINGKATAN PRESTASI BELAJAR PADA MATERI VOLUME KUBUS DAN BALOK DENGAN MENGGUNAKAN METODE COURS REVIEW HORAY - Kusen, - (Universitas Islam Darul Ulum, 2016)
The low achievement of the students in the material of cubes and blocks volume, one reason was the vast majority of teachers do not use the optimal learning method. Not optimal of using media of the teachers in the due to the lack of creative, teachers were too busy in other activities, or also because of the limited ability of teachers themselves. The purpose of the research was to describe the implementation of learning mathematics in calculating basic competence wake volume space by using cours review horay learning method. The research used qualitative descriptive design with classroom action research. Data was collected by observation and tests through two cycles. The results showed that the cours review horay learning method could improve the studentsâ achievement.